Media Pembelajaran Berbasis Motion Graphic Sebagai Alternatif Materi Mesin Esec 3088 Untuk Teknik Manufaktur Elektronika Politeknik Negeri Batam - Pragus Ilham Nayomi; Arta Uly Siahaan (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2021)
The motion graphics that are made are about the ESEC 3088 machine which is used as a circuit packaging machine or what is commonly called IC Packaging. So far, students and lecturers of Electronic Manufacturing Engineering have only used material from the ESEC 3088 machine in pdf and word form obtained from e-learning. From this problem, the author made a study "Motion Graphic-Based Learning Media as an Alternative ESEC 3088 Machine Material for Batam State Polytechnic Electronics Manufacturing Engineering", which aims as an alternative learning media that makes it easier for students to learn the procedures for using the ESEC 3088 machine. Research method The method used is Villamil-Molina's multimedia development method using pre-test and post-test methods, to assess the level of student understanding of the material presented in motion graphics. The results of this study are the results of the post-test test scores which are higher than the pre-test scores, which means that the motion graphics created by the researchers succeeded in increasing the level of students' understanding of the material presented.